Factors Affecting Rice Production in Indonesia - Nina Rifanti; Tri Haryanto (Jurnal Ekuilnomi, 2026)
This study aims to analyze the factors influencing rice production in Indonesia, using secondary data from the Central Statistics Agency (BPS) and the Ministry of Agriculture for the period 2018-2024, covering 30 provinces in Indonesia. The regression model used is the Random Effect Model (REM). The results show that the variables of labor and harvested area have a significant positive effect on rice production, with a very small p-value (p<0.01), indicating that increasing labor and expanding harvested area contribute directly to increasing rice production. In addition, people's business credit shows a positive effect although it is not significant at the 5% level (p=0.139). The variables of fertilizer and staple seeds show a negative effect and are close to being significant at the 10% level, while pump irrigation does not show a significant effect on rice production. This study concludes that factors such as labor and harvested area have a significant impact on increasing rice production, while other factors, such as the use of fertilizer and seeds, show a smaller effect